(untitled) (Journal of Universal Science Research, 2023)
This article is devoted to one of the most important topics in the history of Uzbekistan. In particular, the history of the struggle of our people for their freedom and independence in the 20s of the last century was covered and falsified according to the existing principles of the historiography of that time - the principle of classicism and partisanship. Despite the difficult situation, it was our national intelligentsia, our great-grandfathers, who first of all began to truthfully illuminate the historical truth. Western historians have also carried out considerable scientific research to examine the historical truth on a scientific basis, especially in the coverage of issues related to the policy of bloodshed initiated by the Soviets.